2007
DOI: 10.4049/jimmunol.178.1.186
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of c-Rel in TLR-Induced IL-23 p19 Gene Expression in Dendritic Cells

Abstract: IL-23 plays crucial roles in both immunity against pathogens and autoimmunity against self. Although it is well recognized that IL-23 expression is restricted to the myeloid lineage and is tightly regulated at the transcriptional level, the nature of transcription factors required for IL-23 expression is poorly understood. We report, in this study, that murine dendritic cells deficient in c-Rel, a member of the NF-κB family, are severely compromised in their ability to transcribe the p19 gene, one of the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
112
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 26 publications
14
112
1
1
Order By: Relevance
“…6A), demonstrating that p65 is the critical target for USP7 activity following TNFR activation. Using IL-23p19 promoter reporter plasmids lacking either of two essential NF-κB binding sites (29), we found that expression of USP7 CS does not inhibit LPS-inducible NF-κB-independent transcription (Fig. 6B).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…6A), demonstrating that p65 is the critical target for USP7 activity following TNFR activation. Using IL-23p19 promoter reporter plasmids lacking either of two essential NF-κB binding sites (29), we found that expression of USP7 CS does not inhibit LPS-inducible NF-κB-independent transcription (Fig. 6B).…”
Section: Resultsmentioning
confidence: 95%
“…To determine the degree to which the regulation of TLR-and TNFα-induced gene expression by USP7 is dependent upon its action on p65, we analyzed the effect of the expression of USP7 CS on IL-23p19 promoter reporter activity in WT and p65 −/− MEFs. IL-23p19 promoter activity is largely regulated by NF-κB (29), however when p65 −/− cells are stimulated with TNFα, there remains a significantly lower, but readily detectable, inducible reporter activity compared with WT cells (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Our finding of phosphorylation and nuclear translocation of p65 supports its involvement, and our study does not exclude the involvement of c-Rel, which was shown to be essential in TLRinduced p19 expression in BMDCs. 24 Thus, the sustained Il23a induction in CD40-stimulated BMDCs is apparently supported by switching from a canonical to a non-canonical NF-kB pathway during stimulation. Intriguingly, PGE 2 enhanced both phases of the induction in CD40-stimulated cells through EP4, thus amplifying the production of Il23a mRNA up to ten-fold.…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest that PRDX1 positively regulate c-Rel translation. As c-Rel also regulates the expression of Il12a and Il23a mRNAs (31,32), the levels of both in WT and Prdx1 2/2 BMDMs after LPS stimulation were assayed. The levels of both Il12a and Il23a mRNAs were significantly lower in Prdx1 2/2 than in WT BMDMs (Fig.…”
Section: Low C-rel Induction and P38 Mapk Activation In Lps-stimulatementioning
confidence: 99%